Glycine assists in efficient synthesis of herbal carbon dots with enhanced yield and performance. Issue 34 (19th August 2022) - Cen, Qingyuan; Fu, Fangmei; Xu, Hong; Luo, Lianxiang; Huang, Fanfan; Xiang, Jing; Li, Wei; Pan, Xiaoqin; Zhang, Haoran; Zheng, Mingtao; Zheng, Yinjian; Li, Qingming; et al.
Abstract : As a special type of biomass, herbal medicine often contains a variety of biologically active substances, and taking it as carbon source, it is expected to produce various types of biologically functional carbon dots (CDs). In addition, glycine is helpful to the efficient synthesis of herbal CDs. Abstract : As a special type of biomass, herbal medicine often contains a variety of biologically active substances, and taking it as a carbon source, it is expected to produce various types of biologically functional carbon dots (CDs). However, there are few reports in this field, especially in achieving enhanced performance of CDs by improving the utilization efficiency of active substances in medicinal materials. In this work, by adding glycine as an auxiliary agent in the preparation of CDs from herbal medicine (Exocarpium Citri Grandis), the carboxyl and amino groups of the adjuvant provided more reactive sites, which greatly improved the yield of CDs (about 6 times). More importantly, the antioxidant and biological activities of herbal CDs were also improved. By controlling the functional groups of adjuvants, the effects of carboxyl and amino groups in adjuvants on the synthesis of herbal CDs were compared. The results reveal that both carboxyl and amino groups can react with the substances in the carbon source, and the influence of amino groups was greater. After adding glycine, the size of the CDs became larger, resulting from the more abundant functional groups on the carbon skeleton, which was the main reason for the improved performance of the CDs. Finally, the biological activity experiment demonstrated that CDs derived from Exocarpium Citri Grandis and glycine could greatly enhance the vitality of cells and activate immune cells, which are expected to be applied in the field of cell reproduction and biological immunity. The method proposed in this work provides a potential strategy for high-yield preparation of CDs from biomass.